2016
DOI: 10.1038/srep38633
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence investigation of perfluorinated compounds in surface water from East Lake (Wuhan, China) upon rapid and selective magnetic solid-phase extraction

Abstract: Using a novel magnetic nanocomposite as adsorbent, a convenient and effective magnetic solid-phase extraction (MSPE) procedure was established for selective separation and concentration of nine perfluorinated compounds (PFCs) in surface water sample. Then an ultra high-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) system was employed for detection of PFCs. Good linearity of the developed analytical method was in the range of 0.5–100 ng L−1 with R2 > 0.9917, and the limits of detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 38 publications
0
3
1
1
Order By: Relevance
“…For instance, the ΣPFAA concentrations of Lake Nam Co are slightly lower than those reported for a lake in Longyearbyen, Svalbard Arctic (2495.6 pg/L; Kwok et al, ) but higher than for the Meromictic Lakes in High Arctic Canada (27–754 pg/L; Veillette et al, ). However, the results of the present study are 1 to 2 orders of magnitude lower than those reported for East Lake in central China (30.12–125.35 ng/L; Zhou et al, ) and Washington Park Lake in America (9.49–35.9 ng/L; Kim & Kannan, ). PFBA and PFOS were the dominant compounds in Lake Nam Co, contributing 19% and 17% of all PFAAs, respectively.…”
Section: Resultscontrasting
confidence: 84%
“…For instance, the ΣPFAA concentrations of Lake Nam Co are slightly lower than those reported for a lake in Longyearbyen, Svalbard Arctic (2495.6 pg/L; Kwok et al, ) but higher than for the Meromictic Lakes in High Arctic Canada (27–754 pg/L; Veillette et al, ). However, the results of the present study are 1 to 2 orders of magnitude lower than those reported for East Lake in central China (30.12–125.35 ng/L; Zhou et al, ) and Washington Park Lake in America (9.49–35.9 ng/L; Kim & Kannan, ). PFBA and PFOS were the dominant compounds in Lake Nam Co, contributing 19% and 17% of all PFAAs, respectively.…”
Section: Resultscontrasting
confidence: 84%
“…我国水环境中也普遍存在着PFCs污染问题 表1 [50,57,58] ; 渤海水系的PFCs污染具有显著 的区域差异性, 污染最严重地区检出的PFCs总浓度 比污染程度最低地区的检出浓度高3个数量级 [56] . 濒 临辽宁省和山东省处的渤海中PFCs检出浓度分别为 22.4~26730和11.3~69238 ng L −1 , 比河北省和天津渤海 沿岸高2个数量级, 主要原因可能与在以上地区存在 氟化学工业园区排放的污水有关 [56] .…”
Section: 对较高 例如 美国密歇根洲东北部地下水中的Pfosunclassified
“…In China, the textile, leather and paper production have produced a large number of PFASs since 2003. In 2006, fifteen enterprises produced more than 200 tons of sodiumperfluoro-1-octanesulfonate (PFOS), and in 2010, the associated PFOS output was more than 1 million tons (Zhou et al, 2016). In 2014, limited use of PFOS and its related compounds took effect in China (Mee, 2019).…”
Section: Introductionmentioning
confidence: 99%